Ge/Si and Ge Isotope Fractionation During Glacial and Non-glacial Weathering: Field and Experimental Data From West Greenland - Baronas, J. Jotautas; Hammond, Douglas E.; Bennett, Mia M.; Rouxel, Olivier; Pitcher, Lincoln H.; Smith, Laurence C. (Frontiers in Earth Science, 2021)
Glacial environments offer the opportunity to study the incipient stages of chemical weathering due to the high availability of finely ground sediments, low water temperatures, and typically short rock-water interaction times. In this study we focused on the geochemical behavior of germanium (Ge) in West Greenland, both during subglacial weathering by investigating glacier-fed streams, as well as during a batch reactor experiment by allowing water-sediment interaction for up to 2 years in the laboratory. Sampled in late August 2014, glacial stream Ge and Si concentrations were low, ranging 12-55 pmol/L and 7-33 µmol/L, respectively (Ge/Si = 0.9 - 2.2 µmol/mol, similar to parent rock). As reported previously, the dissolved stable Ge isotope ratio (δ74Ge) of the Watson River was 0.86±0.24‰, the lowest among global rivers and streams measured to date. This value was only slightly heavier than the suspended load (0.48±0.23‰), which is likely representative of the bulk parent rock composition. Despite limited Ge/Si and δ74Ge fractionation, both Ge and Si appear depleted relative to Na during subglacial weathering, which we interpret as the relatively congruent uptake of both phases by amorphous silica (aSi). Continued sediment-water interaction over 470-785 days in the lab resulted in a large increase in dissolved Si concentrations (up to 130-230 µmol/L), a much smaller increase in dissolved Ge (up to 70 pmol/L), resulting in a Ge/Si decrease (to 0.4-0.5 µmol/mol), and a significant increase in δ74Ge (to 1.9-2.2‰). We argue that during the experiment, both Si and Ge are released by the dissolution of previously subglacially formed aSi, and Ge is then incorporated into secondary phases (likely adsorbed to Fe oxyhydroxides), with an associated Δ74Ge_(secondary–dissolved) fractionation factor of -2.15±0.46‰. In summary, we directly demonstrate Ge isotope fractionation during the dissolution-precipitation weathering reactions of natural sediments in the absence of biological Ge and Si uptake, and highlight the significant differences in Ge behavior during subglacial and non-glacial weathering.